(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article is devoted to the analysis of Polish temporal idioms within micro field «childhood» with taking into account three aspects of meaning – significative, denotative and connotative. The role of corpus-based research has been found out to clarify the meanings of the idioms and its place in microfield.